Formal vs. informal coach education - Mallett, C. J.; Trudel, P.; Lyle, J.; Rynne, S. B. (International Journal of Sports Science and Coaching, 2009)
The training of coaches is considered central to sustaining and improving the quality of sports coaching and the ongoing process of professionalisation. Sports coaches participate in a range of learning opportunities (informal to formal) that contribute to their development to varying degrees. In this article, we present our collective understanding on the varying types of learning opportunities and their contribution to coach accreditation and development. The authors presented these views (from a sports pedagogy perspective) as part of a workshop entitled "Formal vs. Informal Coach Education" at the 2007 International Council of Coach Education Master Class in Beijing. These reflections seek to stimulate the on-going, and often sterile, debate about formal versus informal coach education/learning in order to progress scholarship in coaching.